ANALYSIS OF THE RELATIONSHIP BETWEEN CHARACTERISTICS AND MOTIVATIONS OF FOREIGN TOURISTS ON THE DECISION TO STAY AT A HOTEL - Firman Sinaga; I Gusti Made Riko Hendrajana, Firlie Lanovia Amir; Robiatul Adawiyah (Adisam Publisher, 2025)
This study aims to analyze the relationship between the characteristics and motivations of foreign tourists with their decisions in choosing a hotel as a place to stay. The characteristics analyzed include age, gender, income, and cultural origin, while tourist motivations include recreational, business, health, and cultural purposes. This study uses a quantitative method with a survey approach, where data is collected from a number of foreign tourists who stay in various types of hotels. The interaction between tourist characteristics and motivations reveals that these factors do not work separately, but influence each other in the decision-making process. Hotels with relevant facilities and good reputations are more likely to be chosen by foreign tourists, especially if they have positive experiences or receive recommendations from third parties. This study concludes that a deep understanding of tourist characteristics and motivations is key for hotels to develop effective marketing strategies and more personalized services.